Developing Environmental Services in Vietnam - Phuong, Chu Thi Mai; Huong, Nguyen Thi; Anh, Tu Thuy (VNU Journal of Science: Policy and Management Studies; Vol 35 No 2, 2019)
Abstract: In the current trend, human activities of production and activities have discharged a large amount of waste. This makes the pressure to handle environmental pollution increasing. Therefore, environmental services have become an important economic sub-sector of many countries including Vietnam. In Vietnam, as of 2017, have 3,769 enterprises operate in the field of environmental services. Of which, more than 80% are non-state enterprises, about 1% are FDI enterprises and the rest are state-owned enterprises. Enterprises mainly focus on services with high demand resulting from the requirements of the 2005 Law on Environmental Protection, such as designing, manufacturing, and building waste treatment systems; environmental monitoring and analysis; consulting, training, providing environmental information. This paper provides a general analysis of businesses operating in the environmental services industry, the situation of attracting FDI into the industry, pointing out the causes and shortcomings in the development of the industry and giving some discussions and recommendations for developing environmental services in Vietnam. Keywords: Environmental services, FDI, Vietnam. References [1] Trần Hoàn, Hồ Trung Thành, Trương Thị Thanh Huyền, Điều tra đánh giá thực trạng phát triển dịch vụ môi trường ở việt nam và đề xuất các giải pháp phát triển phù hợp với các cam kết quốc tế trong tiến trình hội nhập kinh tế quốc tế, Viện nghiên cứu Thương Mại, Bộ Công Thương, 2007. [2] Tran Hoan, David Luff, Improve negotioation and implementation of international commitments on environmental goods and service, EU-MUTRAP, 2015. [3] David Luff, Nguyen Hoang Minh, Promotion of FDIs in the sector of environmental goods and services, Journal of Environmental Law and Policy, 32(2) (2015) 12-24. [4] WTO, Committee on Trade and Environment in Special Session: Report by the Chairman No. TN/TE/20, WTO, April, 2011. [5] Tổng cục thống kê, Niên giám thống kê, NXB Thống kê, Hà Nội, 2018. [6] Cục đầu tư nước ngoài, Báo cáo tình hình FDI tại Việt Nam 2012-2016, 2017. [7] Tổng cục thống kê, Niên gián Thống kê, NXB Thống kê, Hà Nội, 2014.